Chemical identification of waste cooking oil as additive in Bitumen - Wan Azahar, Wan Nur Aifa; Bujang, Mastura; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Ngadi, Norzita; Mohamad, Mardhiah (Trans Tech Publications, 2016)
The behavior and performance of waste cooking oil (WCO) as an additive and replacement of neat bitumen through the modification of asphalt binder is influenced by its chemical structure and composition. Therefore, the identification of chemical composition inside the WCO-modified bitumen should be identified before any modification is taken that later on will affect its performance. Thus, this paper has emphasized and explained about the chemical composition inside modified bitumen by using WCO. The characterization of each chemical element and functional group of WCO-modified bitumen are conducted by using Gas Chromatography-Mass Selective (GC-MS) and Fourier Transform Infrared Spectroscopy (FTIR). GCMS result showed that the presence of Free Fatty Acid (FFA) in WCO while from the FTIR observation, there are same type of functional group existed in all sample which is C-H bond (alkyl). Through the chemical observation conducted, therefore the chemical alteration is required to improve the performance of WCO in modified bitumen in the future.